Avaliação da influência da fotobiomodulação sobre o remodelamento da matriz extracelular e expressão de citocinas inflamatórias durante o processo de hipertrofia compensatória - Araujo, Andréia Martinelli de Siqueira (2018)
Compensatory hypertrophy occurs due to mechanical overload of the muscle promoting increase in muscle fiber size. Photobiomodulation (PBMT) has demonstrated beneficial effects on muscle tissue during compensatory hypertrophy. The objective of this study was to evaluate the effects of PBMT on the inflammatory markers Interleukin-6 (IL-6) and Tumor Necrosis Factor Alpha (TNF-α) and on the activity of matrix type 2 metalloproteinases (MMP-2) during the rat plantar muscle overload hypertrophy process. Methods: Wistar rats, weighing 250 g, were divided into three groups: control group, hypertrophy group and irradiation hypertrophy group. Hypertrophy was induced through the ablation model of plantar muscle synergists. The irradiation was performed with AsGaAl low-level laser (λ 780 nm; 40mW; energy density 10J/ cm²; 10 seconds each point; 8 points; 3,2J). The groups were evaluated after 7 and 14 days. At the end of the protocol, the plantar muscles were removed and sent for analysis of the inflammatory markers by Elisa and by real-time PCR technique and the activity of MMP-2 by zymography technique. Results: Protein expression increased IL-6 levels in the Hypertrophy + low-level laser theraphy (H + LLLT) group when compared to the hypertrophy group (H), a reduction was observed in the H group when compared to the Control group and reduction of TNF-α in the H and H + LLLT groups when compared to the Control group after 7 days. Gene expression demonstrated an increase of IL-6 in the H + LLLT group when compared to the H group after 14 days and an increase of TNF-α in the H + LLLT group when compared to the H group after 7 days. MMP-2 activity increased in the H and H + LLLT groups when compared to the control group after 7 and 14 days. Conclusion: PBMT in the process compensatory hypertrophy modulated the expression of inflammatory cytokines IL-6 and TNF-α, but did not significantly alter the activity of MMP-2 in the evaluated periods although it showed a tendency to increase after 14 days.